National Institute on Drug Abuse : NIDA - National Institute on Drug Abuse (2016)
[Dt.:] NIDA ist Teil des nationalen Gesundheitsinstitutes des Gesundheitsministeriums der USA. NIDA unterstützt über 85 Prozent der Forschung, die sich mit den gesundheitlichen Aspekten von Drogenmissbrauch beschäftigt. - [Engl.:] The NIDA is a federal-government research institute that is part of the National Institutes of Health, Department of Health and Human Services. NIDA supports over 85 percent of the world's research on the health aspects of drug abuse and addiction